Kesesuaian ekowisata mangrove pada kawasan taman mangrove berbasis pantai di Bontang Kalimantan Timur: The suitability of mangrove ecotourism in beach-based mangrove park areas Bontang Kalimantan Timur - Haris Ardian; Muhammad Yasser; Widya Kusumaningrum (Fakultas Perikanan dan Ilmu Kelautan, Universitas Mulawarman, 2023)
Relatively higher density at tree level was Sonneratia alba, Rhizophora mucronata at sapling and seedling level. The highest relative frequency at the tree level was Sonneratia alba, Rhizophora mucronata at the sapling and seedling level. The highest relative dominance at the tree level was Sonneratia alba, Rhizophora mucronata at the sapling and seedling level. The high mastery of these two types is influenced by environmental factors that support growth. Judging from the Important Value Index of the Coastal Mangrove Park area for the tree level it is Sonneratia alba and at the sapling and seedling level Rhizophora mucronata is dominant. In terms of using the Tourism Suitability Index for the mangrove tourism category, the coastal-free mangrove park area is categorized as appropriate (S2). Based on direct observations, the conditions in the Coastal Mangrove Park area are suitable for ecotourism activities, but it is still necessary to develop sustainable areas and manage the area sustainably. Judging by using the carrying capacity of the area, the area of beach-based mangrove tourism parks in the category of mangrove tourism is 104 people per day, to maintain a mangrove ecosystem in order to remain sustainable it is necessary to know the carrying capacity of an area so that the implementation of visitor restrictions can be estimated for the purpose of keeping the ecotourism area sustainable.